2001
DOI: 10.1097/00006534-200101000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Balance between Proliferation and Apoptotic Cell Death in Fibroblasts Derived from Keloid Lesions

Abstract: A new culture model was developed to study the role of proliferation and apoptosis in the etiology of keloids. Fibroblasts were isolated from the superficial, central, and basal regions of six different keloid lesions by using Dulbecco's Modified Eagle Medium containing 10% fetal calf serum as a culture medium. The growth behavior of each fibroblast fraction was examined in short-term and long-term cultures, and the percentage of apoptotic cells was assessed by in situ end labeling of fragmented DNA. The fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 49 publications
8
130
1
3
Order By: Relevance
“…Whereas the pathophysiological mechanism finally leading to keloid formation remains partially revealed, 8 it is commonly recognized that keloid is a result of the unbalanced cellular dynamics caused by overabundant fibroblast proliferation and insufficient fibroblast apoptosis. 9 In this regard, several studies infer that factors related to tumor formation and cytokine function may play crucial roles in the formation of keloids and influence their development. 10,11 MicroRNAs (miRs) belong to an endogenous class of small non-coding RNAs which function through inhibition of translation levels or fracture of targeted mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the pathophysiological mechanism finally leading to keloid formation remains partially revealed, 8 it is commonly recognized that keloid is a result of the unbalanced cellular dynamics caused by overabundant fibroblast proliferation and insufficient fibroblast apoptosis. 9 In this regard, several studies infer that factors related to tumor formation and cytokine function may play crucial roles in the formation of keloids and influence their development. 10,11 MicroRNAs (miRs) belong to an endogenous class of small non-coding RNAs which function through inhibition of translation levels or fracture of targeted mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study cell-to-cell contact between fibroblasts and mast cells was also (2014) has shown that genetic ablation of connective tissue type mast cells fails to prevent bleomycin induced lung fibrosis [45]. Keloid fibroblasts have been isolated from keloid tissue and grown in cell culture; compared to normal cells keloid fibroblasts have shown differences in growth properties and gene expression [46,47]. Furthermore epigenetic changes have been implicated in the development of fibrosis in keloids [48].…”
mentioning
confidence: 79%
“…The two oncogenes ribosomal protein 18 and Stat-3, both important proteins for cell proliferation, may be linked to keloid pathogenesis (55,56). Another important factor related to keloid formation may be a dysregulation of apoptosis (57,58). If keloid fibroblasts fail to undergo physiologically programmed cell death and, thus, continue to produce and secrete connective tissue beyond the period expected in normal scar formation, the hypertrophic and progressive nature of keloids may result (59).…”
Section: Genetics and Immunologymentioning
confidence: 99%